Preparation of a nanopearl powder/C-HA (chitosan-hyaluronic acid)/rhBMP-2 (recombinant human bone morphogenetic protein-2) composite artificial bone material and a preliminary study of its effects on MC3T3-E1 cells. Issue 6 (1st June 2022) - Zhang, Wenbo; Xu, Pu; Cheng, Yanan; Yang, Yanlan; Mao, Qiuhua; Chen, Zuogeng
ABSTRACT: A nanopearl powder/C-HA (chitosan-hyaluronic acid)/rhBMP-2 (recombinant human bone morphogenetic protein-2) composite artificial bone material was prepared, and its biological properties were evaluated. The nanopearl powder/C-HA/rhBMP-2 composite porous artificial bone material was prepared using the freeze-drying method after the nanopearl powder was prepared using mechanical ball milling. The particle was measured with a transmission electron microscope, its surface morphology and pore size were observed under a scanning electron microscope. The porosity of the artificial bone was determined using pycnometry, a compression performance test was conducted with a universal testing machine, and XRD (X-ray diffraction) patterns were recorded to examine the crystal form of the pearl powder in the composite artificial bone. Finally, the artificial bone was cocultured with mouse MC3T3-E1 cells to investigate its effects on cell proliferation and differentiation and the expression of osteogenesis-related genes. The pearl powder prepared in this experiment had a particle size in the nanometer range. This nanopearl powder, along with C-HA and rhBMP-2, was compounded into the nanopearl powder/C-HA/rhBMP-2 composite artificial bone, showing pore sizes of 188.53 ± 15.32 μm, a porosity of 86.43 ± 2.78% and a compressive strength of 0.342 ± 0.024 MPa. Notably, rhBMP-2 was released from the artificial bone in a sustained manner. Moreover, this artificial bone promoted the adhesion, proliferation, and differentiation of MC3T3-E1 cells and upregulated the expression of ColαI (collagen α1), OCN (osteocalcin), OPN (osteopontin) and Runx2 (runt-related gene 2). Conclusively, this nanopearl powder/C-HA/rhBMP-2 composite artificial bone material showed good performance and cytocompatibility, suggesting that it can be used for bone tissue engineering. GRAPHICAL ABSTRACT: uf0001